The The Influence of Occupational Safety and Health Behavior On Work Accidents Among Health Workers In Public Hospital X In 2025 - Aykel Vindo Ibrena Daeli; Eygia Nina Br Sinulingga (Bhamada Occupational Health and Safety Environment Journal, 2026)
Background: Occupational Health and Safety (OHS) in hospitals is a critical aspect for preventing occupational accidents and work-related diseases that impact healthcare personnel, patients, and the environment. This study aimed to examine the influence of OHS behavior, encompassing knowledge, attitude, and actions, on the incidence of workplace accidents among healthcare personnel at Public Hospital X in 2025. Method: A quantitative research design with a cross-sectional approach was employed. The study involved 100 respondents, consisting of nurses and midwives, selected using stratified random sampling. Data were analyzed using univariate and bivariate statistics, specifically the chi-square test, with a significance level set at p < 0.05. Results: The findings demonstrated a significant influence of OHS knowledge (p = 0.001), OHS attitude (p = 0.001), and OHS actions (p = 0.001) on the occurrence of workplace accidents among healthcare personnel. This underscores the critical role of OHS behavioral aspects in enhancing the occupational safety of healthcare workers in hospitals. Conclusion: The study concludes that improving OHS knowledge, fostering a positive attitude, and ensuring appropriate actions regarding OHS can significantly reduce the risk of workplace accidents. It is therefore recommended that hospitals strengthen OHS training and education and consistently enforce safety protocols to minimize the incidence of workplace accidents within the hospital environment.